Confinement Mechanism in the Field Correlator Method - Yu. A. Simonov; V. I. Shevchenko (Advances in High Energy Physics)
Confinement in QCD results from special properties of vacuum fluctuations of gluon fields. There are two numerically different scales, characterizing nonperturbative QCD vacuum dynamics: “small” one, corresponding to gluon condensate, critical temperature etc, which is about 0.1–0.3 GeV, and a “large” one, given by inverse confining string width, glueball and gluelump masses, and so forth, which is about 1.5–2.5 GeV. We discuss the origin of this hierarchy in a picture where confinement is ensured by quadratic colorelectric field correlators of the special type. These correlators, on the other hand, can be calculated via gluelump Green's function, whose dynamics is defined by the correlators themselves. In this way one obtains a self-consistent scheme, where string tension can be expressed in terms of ΛQCD.